Performance analysis of UWB-IR anti-intercepting communication based on chaotic mapping - MA Long1; WANG Ting-chang2 (Tongxin xuebao)
UWB-IR technology has been concerned in military communications in recent years because of its high data rate,low power consumption,low probability of detection and low probability of interception.By applying the chaos mapping into the UWB-IR was applied and proposed a novel module for chaos modulation and demodulation was proposed,which enhances both the capability of anti-detecting and the capability of anti-intercepting of the UWB-IR.Furthermore,The feasibility of this application was verified.through simulations